Plasma Low-Density Lipoprotein Cholesterol Correlates With Heart Function in Individuals With Type 2 Diabetes Mellitus: A Cross-Sectional Study - Cheng, Po-Chung; Hsu, Shang-Ren; Li, Jung-Chi; Chen, Ching-Pei; Chien, Szu-Chi; Tu, Shih-Te; Cheng, Yun-Chung; Liu, Yu-Hsiu; Kuo, Jeng-Fu (Frontiers in Endocrinology, 2019)
Background Heart failure is a frequent complication of type 2 diabetes mellitus (T2DM). Plasma cholesterol, particularly the proatherogenic low-density lipoprotein (LDL) cholesterol, impairs heart function by promoting atheroma formation and ventricular dysfunction. Considering the established effect of cholesterol on the cardiovascular system, we hypothesized that plasma LDL cholesterol may influence left ventricular function in individuals with T2DM. Methods This cross-sectional study was conducted at a tertiary care hospital in Taiwan. Enrollment criteria were patients exceeding 21 years of age with T2DM who received antidiabetic and cholesterol-lowering medications. Candidates were excluded if they had heart failure, acute cardiovascular events, or familial hypercholesterolemia. Participants received blood sampling for plasma lipids after a 12-hour fast, followed by transthoracic echocardiography in the cardiology clinic. Results The study enrolled 118 participants who were divided into two groups according to their plasma LDL cholesterol levels. Demographic characteristics including age (69.7 years vs. 66.9 years, P = 0.159), body mass index (26.2 kg/m2 vs. 25.9 kg/m2, P = 0.66), diabetes duration (5.4 years vs. 5.1 years, P = 0.48), hemoglobin A1c (7.2 % vs. 7.5 %, P = 0.225), and systolic blood pressure (129 mm Hg vs. 130 mm Hg, P =0.735) were similar between these groups. Moreover, all participants received similar antihypertensive medications. Participants with lower plasma LDL cholesterol levels had better heart function, as measured by the left ventricular ejection fraction (LVEF), than patients with higher LDL cholesterol levels (58.0 % vs. 50.5 %, P = 0.022). Multivariate regression analysis also showed an inverse correlation between plasma LDL cholesterol and left ventricular function (β coefficient: -0.110, P = 0.024). Conclusion This study observed an inverse correlation between plasma LDL cholesterol and heart function in individuals with T2DM. Patients with higher levels of plasma LDL cholesterol had worse left ventricular function. Therefore, plasma LDL cholesterol may be a modifiable risk factor of heart failure in diabetes, but prospective studies are necessary to confirm this finding.